Casticin as potential anticancer agent: recent advancements in multi-mechanistic approaches - Carbone, Katya; Gervasi, Fabio; Kozhamzharova, Latipa; Altybaeva, Nazgul; Sönmez Gürer, Eda; Sharifi-Rad, Javad; Hano, Christophe; Calina, Daniela (Frontiers in Molecular Biosciences, 2023)
Plants, with their range of pharmacologically active molecules, represent the most promising source for the production of new anticancer drugs and for the formulation of adjuvants in chemotherapy treatments to reduce drug content and/or counteract the side effects of chemotherapy. Casticin is a major bioactive flavonoid isolated from several plants, mainly from the Vitex species. This compound is well known for its anti-inflammatory and antioxidant properties, which are mainly exploited in traditional medicine. Recently, the antineoplastic potential of casticin has attracted the attention of the scientific community for its ability to target multiple cancer pathways. The purpose of this review is, therefore, to present and critically analyze the antineoplastic potential of casticin, highlighting the molecular pathways underlying its antitumor effects. Bibliometric data were extracted from the Scopus database using the search strings “casticin” and “cancer” and analyzed using VOSviewer software to generate network maps to visualize the results. Overall, more than 50% of the articles were published since 2018 and even more recent studies have expanded the knowledge of casticin’s antitumor activity by adding interesting new mechanisms of action as a topoisomerase IIα inhibitor, DNA methylase 1 inhibitor, and an upregulator of the onco-suppressive miR-338-3p. Casticin counteracts cancer progression through the induction of apoptosis, cell cycle arrest, and metastasis arrest, acting on several pathways that are generally dysregulated in different types of cancer. In addition, they highlight that casticin can be considered as a promising epigenetic drug candidate to target not only cancer cells but also cancer stem-like cells.